2018
DOI: 10.1159/000496151
|View full text |Cite
|
Sign up to set email alerts
|

Cuff-Based Oscillometric Measurements of Central Hemodynamics: Factors Influencing Central Augmentation Pressure in Normotensive Japanese Individuals

Abstract: Background: Recently, new devices using oscillometric cuff have been developed to derive central blood pressure (BP) waveform from brachial BP waveform. Late systolic pressure augmentation of central BP waveform is a marker of central hemodynamics. Mobil-O-Graph, a cuff-based oscillometric device, can assess central augmentation pressure (AP) together with central BP. Central AP measurement using the Mobil-O-Graph in the European population was reported to be associated with age and sex. However, factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…With respect to AIx measurement, the Mobil-O-Graph reportedly showed a low agreement with Arteriograph ( r = 0.007, p = 0.924) and Complior ( r = 0.135, p = 0.05) in a previous study [12]. In that study, the average AIx measured by the Mobil-O-Graph in 211 individuals (age, 55.1 ± 14.1 years; 67.8% men; 50.2% hypertensive patients) was 17.8 ± 11.3%, which seemed lower than that in our study (32.7 ± 13.4%) but similar to that formerly reported in another study on normotensive men (16.8 ± 7.3%) [15]. Another study on subjects who were almost the same age (53.9 ± 7.9 years) as those in the aforementioned study with a normal cardiac-ankle vascular index score (no probable atherosclerosis) showed that the average AIx measured by the Mobil-O-Graph was 23.76 ± 14.49% [23].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…With respect to AIx measurement, the Mobil-O-Graph reportedly showed a low agreement with Arteriograph ( r = 0.007, p = 0.924) and Complior ( r = 0.135, p = 0.05) in a previous study [12]. In that study, the average AIx measured by the Mobil-O-Graph in 211 individuals (age, 55.1 ± 14.1 years; 67.8% men; 50.2% hypertensive patients) was 17.8 ± 11.3%, which seemed lower than that in our study (32.7 ± 13.4%) but similar to that formerly reported in another study on normotensive men (16.8 ± 7.3%) [15]. Another study on subjects who were almost the same age (53.9 ± 7.9 years) as those in the aforementioned study with a normal cardiac-ankle vascular index score (no probable atherosclerosis) showed that the average AIx measured by the Mobil-O-Graph was 23.76 ± 14.49% [23].…”
Section: Discussionsupporting
confidence: 88%
“…In this study on hypertensive patients, the AP in men and women was 11.2 ± 6.2 mm Hg and 17.3 ± 8.1 mm Hg, respectively. In our previous study on normotensive individuals, the AP in men and women was 5.5 ± 2.8 mm Hg and 11.0 ± 4.7 mm Hg, respectively [15]. The AP in both sexes in this study was expected to be higher than that in normotensive men.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations